Interaction of architecture and society: public procurement as tool to improve local economy and architecture - Jakaitis, Jonas (Journal of Architecture and Urbanism, 2008)
One of the main tasks of public authorities is to find ways how, in the course of the development of urban architecture, to manage and create assumptions for the public to become a new-type, active and cooperative civic society taking part in urban development processes. The research of these problems is important seeking to ensure sustainability in natural, economic-social environment and urban architecture. Assessing the features for application of democratic principles in planning in Lithuania the main objective of this paper is to try to reveal the problems of quality in the development of urban architecture in the context of public procurement of services and to assess the efficiency of procedures defined by legal acts from the viewpoint of architectural quality. Interdisciplinary, comparative analysis methods are used to achieve this objective by revealing the particularity of momentary events.The paper is prepared on the basis of URBACT/LCS (Leveraging City Services) conference of November 2007 (Hudson 2007) (Jakaitis 2007); besides, analysis by S. Mockaitis of Vilnius City Municipality practical experience was used.Architektūros ir visuomenės sąveika: viešieji pirkimai kaip priemonė gerinant vietinę ekonomiką ir architektūrąSantrauka. Vienas iš pagrindinių valdžios institucijų uždavinių – rasti būdų, kaip formuojant miesto architektūrą valdyti procesus ir sudaryti prielaidas visuomenei tapti naujo tipo aktyviai bendradarbiaujančia, dalyvaujančia miesto kūrimo procese pilietine visuomene. Šių problemų tyrimas yra svarbus siekiant gamtinės, ekonominės ir socialinės aplinkos, miestų architektūros darnos. Pagrindinis šio straipsnio tikslas – įvertinant demokratinių planavimo principų Lietuvoje taikymo ypatumus pabandyti atskleisti miestų architektūros formavimo kokybės problematiką viešųjų paslaugų pirkimų kontekste, įvertinti teisės aktais apibrėžtų procedūrų efektyvumą architektūrinės kokybės požiūriu. Šiam tikslui pasiekti taikomi tarpdisciplininis, lyginamosios analizės metodai atskleidžiant dabartinių įvykių specifiką.Reikšminiai žodžiai: miestų architektūros formavimas; viešieji paslaugų pirkimai; darnioji teritorijų plėtra; visuomenės dalyvavimas planavimo procese; miestų architektūros formavimo kompleksiškumas ir integruotas valdymas.First Published Online: 22 May 2013